Numerical investigation of conveyor wing shape type effect on ocean waste collection behavior - Sugianto Erik (EDP Sciences, 2021)
In this paper, an attempt has been made to assess how effective waste-collecting uses the conveyor wing. This wing-equipped conveyor will later be installed in front of the ship. In this work, a simulation model is a conveyor and wing without the ship. A numerical investigation based on Reynolds Averaged Navier Stokes (RANS) for predicting the flow pattern characteristics, velocity contour, and resistance. The focus of the present study is the impact of wing shape on waste collection in calm water through the application of numerical methods. The three variations of wing shape used are solid wing shape, square hollow wing shape, and circle hollow wing shape. It is done using speed variations of 1 to 12 knots. From the analysis of velocity contour, circle hollow wing is faster in collecting waste, then followed by hollow square wing and solid wing. From the flow pattern analysis, the circle hollow wing model is easier to make ocean waste come closer to the winged conveyor than the square wing and solid wing model. It is known that winged conveyors can only be used to collect ocean waste at low speeds. Then based on resistance comparison, it is also known that the resistance of winged conveyors from the largest to the smallest is the solid wing, hollow circle wing, and hollow square wing, respectively.